2005
DOI: 10.1021/jp051318m
|View full text |Cite
|
Sign up to set email alerts
|

Low-Pressure DC Air Plasmas. Investigation of Neutral and Ion Chemistry

Abstract: The neutral and charged species present in a direct current (dc) hollow cathode, gas flow, air reactor are experimentally studied by quadrupole mass spectrometry. The degree of ionization of the plasma and the electron mean temperature with decreasing air pressure, for constant discharge current, are measured with a double Langmuir probe. The chemical composition of the plasma changes appreciably over the 3 x 10(-3) to 5 x 10(-2) mbar range investigated: at the lowest pressures studied, O2 dissociation is up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 69 publications
3
56
0
Order By: Relevance
“…The experimental plasma reactor, shown in Figure 1, is basically the same as in our previous works on air plasmas 34 and H 2 + CH 4 + N 2 plasmas. 35,36 It consists of a grounded cylindrical stainless steel vessel (10 cm diameter, 34 cm length) and a central anode.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental plasma reactor, shown in Figure 1, is basically the same as in our previous works on air plasmas 34 and H 2 + CH 4 + N 2 plasmas. 35,36 It consists of a grounded cylindrical stainless steel vessel (10 cm diameter, 34 cm length) and a central anode.…”
Section: Methodsmentioning
confidence: 99%
“…The reactor was electrically fed by a 0.2 A, 2000V, dc source through a 100 Ω ballast resistor. At the lowest operating pressures, an electron gun built in the laboratory 34 was used for ignition of the plasma. Steady-state plasma currents, I p ≈ 150 mA in the abnormal glow discharge mode, with output source voltages ∼400-460 V, were maintained during the experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DC plasma reactor used for the experiments has been described in previous works [33,34]. It consists of a stainless steel grounded hollow cathode reactor (34 cm length, 10 cm diameter) with a central anode.…”
Section: Methodsmentioning
confidence: 99%
“…In the steady state, a small fraction of these hot atoms survives and can be detected either in the line profiles of Balmer emission lines of H atoms [81] or indirectly in the energy resolved mass spectra of H + and O + ions [81][82][83]. However, previous works carried out on this reactor for different gas mixtures at comparable pressures [33,34,[36][37][38][39] have shown that the assumption of a Maxwellian distribution is not a bad approximation for the global kinetics, and we have adopted it here for lack of better information on the actual eedf. The limitations of this approximation should be taken into account in the interpretation of the results.…”
Section: Modelmentioning
confidence: 99%